1996
DOI: 10.1901/jaba.1996.29-53
|View full text |Cite
|
Sign up to set email alerts
|

Peer Modeling of Response Chains: Observational Learning by Students With Disabilities

Abstract: Peer models (classmates without disabilities) who were proficient in performing a task completed one response chain each day and described the steps they performed while their classmates with disabilities observed. Three students with disabilities participated, and their performance of the response chains was assessed immediately prior to and following the peer modeling each day. A multiple probe design across response chains, replicated across children with disabilities, was used. In addition, participation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 17 publications
0
40
0
2
Order By: Relevance
“…Griffen, Wolery, and Schuster (1992) found that students with mental retardation who could not perform a chained food preparation task did so after observing it completed by a peer who was directly taught using a zero-second time delay procedure. This finding was replicated by Werts, Caldwell, and Wolery (1996), who found that students with disabilities who could not perform a task showed higher accuracy after observing a typically developing peer emit the chains accurately. Children with autism demonstrated color discriminations after observing typically developing students perform color discrimination tasks (Egel, Richman, & Koegel, 1981).…”
mentioning
confidence: 75%
“…Griffen, Wolery, and Schuster (1992) found that students with mental retardation who could not perform a chained food preparation task did so after observing it completed by a peer who was directly taught using a zero-second time delay procedure. This finding was replicated by Werts, Caldwell, and Wolery (1996), who found that students with disabilities who could not perform a task showed higher accuracy after observing a typically developing peer emit the chains accurately. Children with autism demonstrated color discriminations after observing typically developing students perform color discrimination tasks (Egel, Richman, & Koegel, 1981).…”
mentioning
confidence: 75%
“…These skills included receptive labels (Charlop et al 1983;Rehfeldt et al 2003), expressive labels (Coleman and Stedman 1974;Leaf et al 2013), voice volume (Coleman and Stedman 1974), play (Colozzi et al 2008;Tyron and Keane 1986), various discriminations (Egel et al 1981;Varni et al 1979), imitation (Ganz et al 2008), general knowledge skills (Ihrig and Wolchik 1988), conditioning preferences/ reinforcers (Leaf et al 2012;Singer-Dudek and Oblak 2013), job functions (Leaf et al 2013), inferences (Leaf et al 2013), sight words (Ledford et al 2008), monitoring response (Pereira-Delgado and Greer 2009; , reading (Rehfeldt et al 2003), picture to word/word to picture matching (Rehfeldt et al 2003), eating (Sira and Fryling 2012), food and drink prep (Tekin-Iftar and Birkan 2010), sign language (Venn et al 1996), spelling (Werts et al 1996), playing an audiotape (Werts et al 1996), using a calculator (Werts et al 1996), and social communication (Wilson 2013).…”
Section: Skill(s) Measuredmentioning
confidence: 99%
“…A majority of the studies, 16 (80 %), utilized peer models (Charlop et al 1983;Coleman and Stedman 1974;Colozzi et al 2008;Egel et al 1981;Ganz et al 2008;Leaf et al 2013;Ledford et al 2008;Pereira-Delgado and Greer 2009;Rehfeldt et al 2003;Singer-Dudek and Oblak 2013;Sira and Fryling 2012;Tekin-Iftar and Birkan 2010;Tyron and Keane 1986;Venn et al 1996;Werts et al 1996), while 3 studies utilized adult models (Leaf et al 2012;Varni et al 1979;Wilson 2013). One study utilized both adult and peer models in an effort to compare the effectiveness of the two different types of models (Ihrig and Wolchik 1988).…”
Section: Model and Formatmentioning
confidence: 99%
“…At some level, peer modeling is powerful (Werts, Caldwell & Wolery, 1996). People model others throughout life, and one's characteristics do influence the degree to which modeling takes place (Marvin, 1980).…”
Section: Adult Observational Learningmentioning
confidence: 99%